Protocol for the Functional Analysis of Prosthesis in Patients with Partial Foot Amputation - Hernández - Castillo, A.; Álvarez - Camacho, M; Sánchez - Arévalo, F. M. (Revista Mexicana de Ingenieria Biomedica, 2013)
At present, the development of prostheses presents problems that have yet to be completely solved. Despite that various studies have been developed to evaluate the functioning of these prostheses, the works presented in the literature are conducted with suppositions of burden, of materials, and are even practiced under static conditions. The technique of Digital image correlation (DIC) has been used in diverse applications, but has been scarcely explored in the ambiance of prostheses. In this work, we present a technique capable of measuring the real deformation of prosthetic systems in patients with amputations, under real conditions of load and posture. Employing the DIC method, it is possible to evaluate a patient?s prosthesis without the need for instrumenting or modifying it. In addition, it is possible to know the main points of deformation without having to ultimate load the piece. With this technique, it is possible to measure the prosthetic system?s main deformation zones, with the advantage that evaluation can be performed by applying the real loads and postures of a patient in a dynamic analysis.